PENGEMBANGAN BAHAN AJAR MULTIMEDIA INTERAKTIF SISPERMA DENGAN PENDEKATAN DIFERENSIASI UNTUK MENINGKATKAN MINAT BELAJAR IPAS SISWA KELAS 5 SD - Thohir, M. Anas; Jatayu, Putri Dataliya; Wilujeng, Rahma Islamiati; Nadia, Rifdah; Hidayah, Rizqi Nurul; Miranti, Sinta Dwi; Rahma, Selin Dita (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This research aims to develop interactive multimedia teaching materials with a differentiation approach to increase 5th grade students' learning interest in the Natural and Social Development Sciences (IPAS) subject of the Human Respiratory System. The research method used is Research and Development (R&D), with the ADDIE development model that considers diverse student learning styles. SISPERMA teaching materials were developed according to the needs of elementary schools which still lack the provision of interactive multimedia teaching materials. The instruments used include a learning interest questionnaire, observation sheets to assess student activity, interviews to obtain feedback from teachers and students, as well as documentation of learning processes and outcomes. Data collection techniques include observation, filling out questionnaires, interviews, and analysis of the results of documentation and implementation of teaching materials. The research results show that interactive multimedia teaching materials are effective in increasing students' interest in learning. The use of these teaching materials is significant in increasing students' interest in learning, with higher enthusiasm during learning. The differentiation approach allows students to learn according to their learning style, making the material more interesting and dynamic. This research concludes that teaching materials SISPERMA Differentiation-based is effective in improving the quality of science and science learning, especially regarding the respiratory system material for grade 5 elementary school students.